Scale sensor: Rapid monitoring of scale deposition and inhibition using fiber optics in a geothermal system and comparison with other monitoring devices. (June 2021) - Okazaki, Takuya; Kuramitz, Hideki; Watanabe, Tomoaki; Ueda, Akira
Highlights: A scale sensor is a newly developed fiber optics based scale evaluation method. The performance of scale sensor was compared with other monitoring devices using the same test waters. Rapid assessment of silica deposition effects for geothermal brines is possible within a period of several hours. High-temperature (< 300 °C) monitoring can be performed by the scale sensor. Abstract: A scale sensor was a newly developed using fiber optics to evaluate scale deposition that occurs at hot spring waters and geothermal brines. This proposed sensor is also capable of assessing the effect of various scale suppression methods. The sensor is fabricated by removing the cladding of a multimode fiber to expose the silica core which then detects the scale deposition from the changes in the refractive index. The effectiveness of the proposed sensor was validated using the carbonated water samples at Matsushiro Hot Spring in Nagano Prefecture and brines from three geothermal power stations in Japan. A comparative performance evaluation between the proposed scale sensor and other monitoring devices were investigated at the same locations. The result of the analysis clearly indicates that the silica deposition and depression effects for geothermal brines under standard atmospheric conditions is rapid, ranging from several hours to half a day by the scale sensor. From the results obtained at the Sumikawa geothermal power station, it was found that the silica scale deposition can be sufficiently evaluated by a scale sensor even at high temperatures and pressure.